Keeping the World's Environment under Review An Intellectual History of the Global Environment Outlook - Bakkes, Jan (Central European University Press, 2022)
How do we take stock of the state and direction of the world's environment, and what can we learn from the experience? Among the myriad detailed narratives about the condition of the planet, the Global Environment Outlook (GEO) reports-issued by the United Nations Environment Programme-stand out as the most ambitious. For nearly three decades the GEO project has not only delivered iconic global assessment reports, but through its multitude of contributors has inspired hundreds of similar processes worldwide from the regional to the local level. This book provides an inside account of the evolution of the GEO project from its earliest days. Building on meticulous research, including interviews with former heads of the United Nations Environment Programme, diplomats, leading contributing scientists, and senior leaders of collaborating organizations, the story is told from the perspective of five GEO veterans who all played a pivotal role in shaping the periodic assessments. The GEO's history provides striking insights and will save valuable time to those who commission, design and conduct, as well as critique and improve, assessments of environmental development in the next decade.